Collecting Microplastics in Gardens: Case Study (i) of Soil - Sobhani, Zahra; Luo, Yunlong; Gibson, Christopher T.; Tang, Youhong; Naidu, Ravi; Megharaj, Mallavarapu; Fang, Cheng (Frontiers in Environmental Science, 2021)
As an emerging contaminant, microplastic is receiving increasing attention. However, the contamination source is not fully known and new source is still being identified. Herewith we report that microplastics can be found in our garden, either due to the wrong-doing by leaving plastics bubble wrap to be mixed with mulch or due to the use of plastic landscape fabric to bed the mulch. In the beginning, they were at big sizes, such as > 5 mm. However, after 7 years in garden due to natural degradation, weathering or abrasion, microplastics are released. We categorise the plastic fragments into different groups, 5 mm – 0.75 mm, 0.75 mm – 100 m, and 100 m – 0.8 m, using filters including kitchenware, meaning we can catch microplastics in our garden by ourselves. We then characterised the plastics using Raman image mapping and a logic-based algorithm to increase the signal-noise ratio and the image certainty. This is because the signal-noise ratio from a single Raman spectrum, or even from an individual peak, is significantly less than that from a spectrum matrix of Raman mapping (such as 1 vs. 50  50) that contains 2,500 spectra, from a statistic point of view. From the 10 gram soil we sampled, we could detect the microplastics, including big (5 mm – 100 m) fragments and small (< 100 m) ones, suggesting the degradation fate of plastic in our garden. Overall, these results warn us that we must be careful when we do gardening including selection of plastic items for gardens.